Estimation of Serum Magnesium in Bangladeshi Gestational Diabetic Mother (Anwer Khan Modern Medical College Journal, 2018)
Background: Gestational diabetes mellitus (GDM) is characterized by glucose intolerance during pregnancy.GDM is associated with an increased incidence of congenital abnormalities usually aggravated by maternal magnesium deficiency. Magnesium is one of the essential trace elements for normal embryogenesis and foetal growth and its deficiency increase mortality and morbidity rate of mothers, embryos and neonates.Objective: To evaluate the association of serum magnesium with GDM in second and third trimester. Materials & Methods: This case control study was conducted in Mymensingh Medical College Hospital during the period from July 2013 to June 2014 to evaluate the association of magnesium with GDM in Bangladeshi women. A total number of 172 subjects were participated in this study; among them eighty six women diagnosed with GDM were selected as case (Group-I) and eighty six healthy pregnant women were control (Group-II). The case group again subdivided as Group Ia and Ib second and third trimester respectively. Control group also subdivided as Group IIa and IIb second and third trimester respectively. Student's unpaired t test was used to analyse the data between groups. For analytical purpose 95% confidence limit (p